Organizational Learning, Proprietary Technology, And Manufacturing Performance - Ng, Good Ching (2003)
The objective of this research is to study how manufacturing firms develop capabilities and resources that are inimitable, and non-substitutable in pursuit of higher performance and competitive advantage. This research attempts to find out: firstly, whether organizational learning leads to proprietary technology development; secondly, whether proprietary technology development leads to manufacturing performance; lastly, whether organizational learning leads to manufacturing performance via proprietary technology development. Data were collected from a sample of sixty-eight lower to top-level managers in manufacturing firms in the Northern of Peninsular Malaysia. The findings have resulted in substantial acceptance of the hypotheses formulated. The results of this study indicates that the internal learning will lead to more proprietary technology development and in tum proprietary technology will lead to high level of manufacturing performance.